Depressão endogâmica em pepino caipira - Godoy, Amanda Regina [UNESP] (2004)
The objective of this work was evaluate the inbreeding depression with successive generations of self-pollination in a cucumber caipira population (S0, S1, S2, S3; S4 e S5), obtained by crossing Safira x Hatem hybrids. Two experiments were accomplished: one to evaluate immature fruits production and another to analyze the mature fruits production, seed quality and yield. The experimental design of both experiments were randomized blocks, in the first with seven treatments (different generations of self pollination - S0 to S5 and the hybrid Safira), six replicates and five plants per plot and in the second the same seven treatments, four replicates and five plants per plot. In the first experiment (immature fruits) was number of leaves, length of the main stem, number and weight of fruits, total and commercial, number of nodes and vines percentage were evaluated. In the second experiment (mature fruit) the following traits were evaluated characteristic: seed number and weight per plant and per fruit and seed quality (germination test, first counted of seeds, index of germination speed and weight of 100 seeds). The averages were compared by the Tukey test (5%) and the evaluation of the inbreeding depression was made with regression analysis. In the experiment 1 smaller production of fruits was observed (total and commercial) starting from population S2, demonstrating possible vigor loss. The populations S0 and S1 were similar or superiors for the characteristics number of total fruits, total weight per plant and commercial weight per plant when compared to the hybrid Safira, demonstrating the potencial of this population to obtain a new cultivar or hybrid of the caipira type. The experiment two there was no statistical difference for all the appraised characteristics, showing that the inbreeding didn`t affect the production and quality of the seeds in this population.